Morphological characteristics of subaxial cervical pedicles and surrounding critical structures in patients with vertebral artery dominance - an anatomical study based on computed tomographic imaging - Jin Yang; Tao Li; Qing Wang; Gaoju Wang; Song Wang; Shuang Xu; Shuai Zhang; Qiuhan Li (BMC Musculoskeletal Disorders, 2022)
Abstract Background No study has assessed the feasibility and safety of cervical pedicle screw implantation in patients with vertebral artery dominance (VAD), a common vertebral artery (VA) variation which can increase VA injury (VAI) risk. This study was to assess morphological characteristics of the subaxial cervical pedicles and surrounding critical structures, and identify their correlations in patients with VAD. Methods Computed tomography arteriography scans of 152 patients were used for retrospectively measuring parameters including pedicle outer width (POW), the distance from the lateral pedicle border to the closest part of VA (DPVA), diameter of VA (DVA), area of VA (AVA), area of transverse foramen (ATF) and occupational ratio of transverse foramen (TF). Moreover, correlations among some critical parameters were assessed. Results One hundred eight males and 44 females, with a mean age of 55.9 years were included. POW was smaller on the dominant side than on the non-dominant side, whereas DPVA, DVA, AVA, ATF, and TF were larger on the dominant side than those on the non-dominant side. On both sides, POW < 4 mm and POW + DPVA < 5 mm were observed most frequently at C3 and C4. On both sides, POW was correlated to ATF, and ATF was correlated to DVA and AVA. DPVA was correlated to ATF on the dominant side. Conclusion Patients with VAD exhibited smaller POW on the dominant side, most frequently at C3 and C4. Dominant VA may indirectly affect POW. TF may be a key determinant of DPVA and POW.